High‐entropy alloy catalysts: From bulk to nano toward highly efficient carbon and nitrogen catalysis - Lanlan Yu; Kaizhu Zeng; Chenghang Li; Xiaorong Lin; Hanwen Liu; Wenhui Shi; Hua‐Jun Qiu; Yifei Yuan; Yonggang Yao (Carbon Energy, 2022)
Abstract High‐entropy alloys (HEAs) have attracted widespread attention as both structural and functional materials owing to their huge multielement composition space and unique high‐entropy mixing structure. Recently, emerging HEAs, either in nano or highly porous bulk forms, are developed and utilized for various catalytic and clean energy applications with superior activity and remarkable durability. Being catalysts, HEAs possess some unique advantages, including (1) a multielement composition space for the discovery of new catalysts and fine‐tuning of surface adsorption (i.e., activity and selectivity), (2) diverse active sites derived from the random multielement mixing that are especially suitable for multistep catalysis, and (3) a high‐entropy stabilized structure that improves the structural durability in harsh catalytic environments. Benefited from these inherent advantages, HEA catalysts have demonstrated superior catalytic performances and are promising for complex carbon (C) and nitrogen (N) cycle reactions featuring multistep reaction pathways and many different intermediates. However, the design, synthesis, characterization, and understanding of HEA catalysts for C‐ and N‐involved reactions are extremely challenging because of both complex high‐entropy materials and complex reactions. In this review, we present the recent development of HEA catalysts, particularly on their innovative and extensive syntheses, advanced (in situ) characterizations, and applications in complex C and N looping reactions, aiming to provide a focused view on how to utilize intrinsically complex catalysts for these important and complex reactions. In the end, remaining challenges and future directions are proposed to guide the development and application of HEA catalysts for highly efficient energy storage and chemical conversion toward carbon neutrality.